2005
DOI: 10.1021/es0513178
|View full text |Cite
|
Sign up to set email alerts
|

Oral Exposure of PBDE-47 in Fish:  Toxicokinetics and Reproductive Effects in Japanese Medaka (Oryzias latipes) and Fathead Minnows (Pimephales promelas)

Abstract: The toxicokinetics of 2,2,4,4-tetrabromodiphenyl ether (PBDE-47) was studied in the Japanese Medaka (Oryzias latipes) after a single oral exposure followed by termination at specific time points. The effects of repeated oral exposure to PBDE-47 on reproductive performance was assessed using a pair breeding experimental design with fathead minnows (Pimephales promelas) given daily PBDE-47 exposures for 25 days, during which fecundity was measured as an indicator of reproductive performance. Medaka and fathead m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
85
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 26 publications
10
85
1
Order By: Relevance
“…Indeed, very limited information is available on reproductive toxicity of bromophenols, while several studies have been conducted on other brominated flame retardants (BFRs). For example, oral exposure to the PBDE congener 2,2′,4,4′-tetrabromodiphenyl ether (PBDE-47) impaired reproductive activity in fathead minnow (Muirhead et al 2006). Exposure to low doses of 2,2′,4,4′,5-pentabromodiphenyl ether (PBDE-99) during critical periods of development permanently impairs spermatogenesis in adult rat offspring (Kuriyama et al, 2005) and PBDE-99 have also been shown to interfere with sexual development and sexually dimorphic behaviors, both of which are mediated by hormones produced in endocrine glands (Lilienthal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, very limited information is available on reproductive toxicity of bromophenols, while several studies have been conducted on other brominated flame retardants (BFRs). For example, oral exposure to the PBDE congener 2,2′,4,4′-tetrabromodiphenyl ether (PBDE-47) impaired reproductive activity in fathead minnow (Muirhead et al 2006). Exposure to low doses of 2,2′,4,4′,5-pentabromodiphenyl ether (PBDE-99) during critical periods of development permanently impairs spermatogenesis in adult rat offspring (Kuriyama et al, 2005) and PBDE-99 have also been shown to interfere with sexual development and sexually dimorphic behaviors, both of which are mediated by hormones produced in endocrine glands (Lilienthal et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Fish condition factor (Torres et al, 2014-in this issue), often used to assess the overall condition and stoutness of a fish, was not different for LSS among sites (P = 0.3095), likely because sites were differentially influenced by nutrients, chemical mixtures, and hydrology. In an experiment in which adult fathead minnows (Pimephales promelas) were fed daily for 25d with BDE-47, the condition factor of only the males was significantly reduced (P b 0.011) compared with controls (Muirhead et al, 2006). Contrary to that finding, longterm continuous exposure to BDE-209 was related to an increase in the condition factor in adult male zebrafish (Danio rerio), suggesting a potential link with obesity-related genes (He et al, 2011).…”
Section: Fish and Sitesmentioning
confidence: 76%
“…In contrast, chlorpyrifos (an organophosphate insecticide) and current-use pesticides were positively correlated with GSI in this study with LSS (Table 3). Male medaka (Oryzias latipes) GSI was not different between BDE-47-treated fish and controls, although this congener was reproductively toxic in males as noted by a cessation of spawning and a lower percentage of mature spermatozoa (Muirhead et al, 2006). Similarly, BDE-47 was not related to GSI, yet it was negatively correlated with sperm motility in LSS (Table 3).…”
Section: Fish and Sitesmentioning
confidence: 96%
See 1 more Smart Citation
“…The BDE-47 was incorporated into the pelleted trout feed and assayed by GC-ECD using methods described in Muirhead et al (2006) to verify the concentration and stored at −20°C until day of feeding. Each morning of the exposure, a known mass of BDE-47 feed was provided to individual trout.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%